EL ESPERPENTO EN EL CINE DE ÁLEX DE LA IGLESIA - Mg. Marta RIVERO FRANCO (Fonseca, Journal of Communication, 2023)
There are several studies that allude to the presence of esperpento in Álex de la Iglesia films — subject specifically linked to his production and without it this cannot be understood—, but there exist just a few that delve into the way in which this resource is embodied in his creations.